A meteorological discourse on extreme storm events driven by Asian slum emissions. (21st November 2019) - Ghosh, Sat; Gadian, Alan; Dobbie, Steve; Samaddar, Arkayan; Sharma, Anuj; Chandramouli, Pranav; Palsapure, Aditi
Increasingly the world over, climate modellers have suggested that local emissions may well affect cyclonic storms. The eastern coast of India, home to mega cities, is routinely battered by such storms over the period October to December. Additionally, these cities house millions of slum dwellers who cook their meals from unseasoned firewood yielding substantial amounts of biomass particles. These particles chemically age within a polluted air mass rendering them active as cloud condensation nuclei (CCN). This first study shows the genesis, progression and evolution of one such tropical disturbance, Hurricane Thane, which was modulated by these transient emissions, devastating the coast of Tamil Nadu on 30 December 2011. We show that auto-conversion rates converting cloud water to rain water are significantly altered by up to 12% with an increase of 20.5% in the cloud water amounts, when these effects are included